2D Metal‐Organic Framework‐Based Thin‐Film Nanocomposite Membranes for Reverse Osmosis and Organic Solvent Nanofiltration. Issue 11 (7th May 2021) - Li, Feng; Liu, Theo Dongyu; Xie, Silijia; Guan, Jian; Zhang, Sui
Abstract: Metal‐organic frameworks (MOFs) are promising candidates for membrane‐based liquid separations due to their intrinsic microporosity, but many are limited by their insufficient stability. In this work, a copper‐benzoquinoid (Cu‐THQ) MOF was synthesized and demonstrated structural stability in water and organic solvents. After incorporation into the polyamide layer, the hydrophilicity of the membranes was enhanced. The resultant thin‐film nanocomposite (TFN) membranes broke the permeability‐selectivity tradeoff by showing 242 % increase in water permeance and slightly enhanced salt rejection at MOF loading of 0.0192 mg cm −2 . The underlying mechanism was probed by different chemical and morphological characterizations. The membranes also showed improved tolerance to chlorine oxidation. With their excellent stability, the Cu‐THQ MOF‐based membranes further demonstrated impressive performance in organic solvent nanofiltration involving dimethylformamide. Abstract : Fine filtration : A copper‐benzoquinoid (Cu‐THQ) metal‐organic framework (MOF) is incorporated into a polyamide layer. The resulting thin‐film nanocomposite membranes break the permeability‐selectivity trade‐off by showing 242 % increase in water permeance for reverse osmosis. The membranes also demonstrate structural stability with good dimethylformamide permeance during organic solvent nanofiltration.